Guidelines and Good Clinical Practice Recommendations for Contrast Enhanced Ultrasound (CEUS) in the Liver – Update 2020 – WFUMB in Cooperation with EFSUMB, AFSUMB, AIUM, and FLAUS - Dietrich, Christoph F.; Nolsøe, Christian Pállson; Barr, Richard G.; Berzigotti, Annalisa; Burns, Peter N; Cantisani, Vito; Chammas, Maria Cristina; Chaubal, Nitin; Choi, Byung Ihn; Clevert, Dirk-André; Cui, Xinwu; Dong, Yi; D’Onofrio, Mirko; Fowlkes, J. Brian; Gilja, Odd Helge; Huang, Pintong; Ignee, Andre; Jenssen, Christian; Kono, Yuko; Kudo, Masatoshi; Lassau, Nathalie; Lee, Won Jae; Lee, Jae Young; Liang, Ping; Lim, Adrian; Lyshchik, Andrej; Meloni, Maria Franca; Correas, Jean Michel; Minami, Yasunori; Moriyasu, Fuminori; Nicolau, Carlos; Piscaglia, Fabio; Saftoiu, Adrian; Sidhu, Paul S.; Sporea, Ioan; Torzilli, Guido; Xie, Xiaoyan; Zheng, Rongqin (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
The present, updated document describes the fourth iteration of recommendations for the hepatic use of contrast enhanced ultrasound (CEUS), first initiated in 2004 by the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB). The previous updated editions of the guidelines reflected changes in the available contrast agents and updated the guidelines not only for hepatic but also for non-hepatic applications.The 2012 guideline requires updating as previously the differences of the contrast agents were not precisely described and the differences in contrast phases as well as handling were not clearly indicated. In addition, more evidence has been published for all contrast agents. The update also reflects the most recent developments in contrast agents, including the United States Food and Drug Administration (FDA) approval as well as the extensive Asian experience, to produce a truly international perspective.These guidelines and recommendations provide general advice on the use of ultrasound contrast agents (UCA) and are intended to create standard protocols for the use and administration of UCA in liver applications on an international basis to improve the management of patients.
Keywords: contrast enhanced ultrasound (CEUS); World Federation for Ultrasound in Medicine and Biology (WFUMB); guideline; liver